Can the minimum living standard guarantee scheme enable the poor to escape the poverty trap in rural China?. (13th March 2017) - Zhao, Liqiu; Guo, Yu; Shao, Ting
Abstract : The rural Minimum Living Standard Guarantee ( Dibao ) Scheme is the most important social assistance programme in rural China. However, how the rural Dibao programme affects household expenditures and whether it can enable the poor to escape the poverty trap are questions that remain largely unexplored. This study used data from the 2012 Rural Household Survey in China to investigate the impact of the rural Dibao programme on household expenditures. We found that the programme significantly improved the well‐being of low‐income households. Particularly, the programme significantly increased household expenditures on housing, education and health; furthermore, the impact was greater for households with educated household heads. However, the programme did not significantly affect household expenditures on food, transportation or farming inputs. The results imply that participation in the rural Dibao programme induces household investment in human capital, which could help to break the inter‐generational transmission of poverty and raise long‐run welfare.